2019
DOI: 10.3390/polym11091379
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bulky Substituents on Two π-Conjugated Mesogenic Fluorophores. Their Organic Polymers and Zinc-Bridged Luminescent Networks

Abstract: From a dicyano-phenylenevinylene (PV) and an azobenzene (AB) skeleton, two new symmetrical salen dyes were obtained. Terminal bulky substituents able to reduce intermolecular interactions and flexible tails to guarantee solubility were added to the fluorogenic cores. Photochemical performances were investigated on the small molecules in solution, as neat crystals and as dopants in polymeric matrixes. High fluorescence quantum yield in the orange-red region was observed for the brightest emissive films (88% yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 75 publications
(90 reference statements)
0
23
0
Order By: Relevance
“…The intramolecular hydrogen-bond interactions in the half-salen moieties cause the excited-state intramolecular proton-transfer (ESIPT) [60,61] known to lead to emission in solution [46,59,[61][62][63][64][65][66]. The same effect is known to occur in the solid state [12,67] if the intramolecular H-bond produce hindrance to the torsion of sterically encumbered parts of the molecule [57,68,69]. In our case, the acetyl substituents on the furan rings and the bulky naphthol moieties make NBDF a RIR probe.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The intramolecular hydrogen-bond interactions in the half-salen moieties cause the excited-state intramolecular proton-transfer (ESIPT) [60,61] known to lead to emission in solution [46,59,[61][62][63][64][65][66]. The same effect is known to occur in the solid state [12,67] if the intramolecular H-bond produce hindrance to the torsion of sterically encumbered parts of the molecule [57,68,69]. In our case, the acetyl substituents on the furan rings and the bulky naphthol moieties make NBDF a RIR probe.…”
Section: Resultsmentioning
confidence: 70%
“…Compound NBDF is the condensation product between a diamine and a salicylic aldehyde in 1:2 ratio. The probe contains two half-salen [12,[57][58][59] Schiff base sites working as electron-donor arms and an electron-acceptor core. As shown in Scheme 1, the (4-nitrophenyl) benzodifuran unit represents the acceptor moiety due to the strong electron-withdrawing properties of the nitro substituent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Scheme 1, the dyes A1 and A2 were obtained by condensation of the diamino derivative AB-NH 2 [39] with 4-(diethylamino)-2-hydroxybenzaldehyde and 2-hydroxy-4-nitrobenzaldehyde, respectively. Though structurally similar, a different conjugation pattern is recognizable, D-π-D-π-D respectively for A1 and A-π-D-π-A for A2 (where D = electron donor moiety, A = electron acceptor moiety, and π = conjugated system).…”
Section: Synthesis and Optical Behavior Of The Dyes And Their Pvc Blendsmentioning
confidence: 99%
“…Two ESIPT undergoing sites are generated by the condensation of the amino-terminal groups of the precursor AB-NH 2 with the salicylic aldehydes, guaranteeing emission in solution. According to a recent approach [26,39,40], it was found that the fast proton transfer in ESIPT sterically encumbered probes are impeded due to restriction of intramolecular rotation (RIR effect), also providing solid-state emission. The central methoxy groups cause steric hindrance on the conjugated skeleton without too much lowering solubility.…”
Section: Synthesis and Optical Behavior Of The Dyes And Their Pvc Blendsmentioning
confidence: 99%